2018
DOI: 10.1097/igc.0000000000001151
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Node Biopsy in Endometrial Cancer With Dual Cervical and Fundal Indocyanine Green Injection

Abstract: The SLN biopsy with both cervical and fundal ICG injection offers good overall detection rates and improved mapping of the aortic area. The SLN ultrastaging increases the number of nodes considered positive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 37 publications
3
24
0
4
Order By: Relevance
“…The sentinel lymph node ultrastaging increases the number of nodes considered positive. 25 In the current study, we have demonstrated that the lymph node involvement is associated with tumor volume of more than 6 mL, myometrium invasion of more than 50%, the tumor histological grade, and the high CA125. Interestingly, the lymph node involvement was more common in those with diabetes mellitus and hypertension.…”
Section: Discussionsupporting
confidence: 53%
“…The sentinel lymph node ultrastaging increases the number of nodes considered positive. 25 In the current study, we have demonstrated that the lymph node involvement is associated with tumor volume of more than 6 mL, myometrium invasion of more than 50%, the tumor histological grade, and the high CA125. Interestingly, the lymph node involvement was more common in those with diabetes mellitus and hypertension.…”
Section: Discussionsupporting
confidence: 53%
“…In case of doubt (echelon vs true SLN) channels were followed back up to the uterus, to make sure that there were no other nodes between the womb and the supposed SLN. Ruiz et al, in aiming to increase the aortic detection rate, used a dual fundal/cervical injection of ICG and found nearly 60% of aortic mapping 23. A Korean group reported an even higher aortic detection rate (86%) following two-step (corunal and cervical) ICG injection 24.…”
Section: Discussionmentioning
confidence: 99%
“…Dual cervical and fundal indocyanine green injections for endometrial cancer were reported by Ruiz et al28 This study included 69 patients in the high-risk group who underwent full lymphadenectomy, but 42 patients in the low-risk group did not undergo pelvic or para-aortic lymphadenectomy. Para-aortic SLNs were detected in 66 of 111 patients (59%), and four patients (3%) had only para-aortic SLNs without pelvic SLNs.…”
Section: Discussionmentioning
confidence: 99%